Traffic and Granular Flow '13 2014
DOI: 10.1007/978-3-319-10629-8_17
|View full text |Cite
|
Sign up to set email alerts
|

Stair Evacuation Simulation Based on Cellular Automata Model Considering Social Forces

Abstract: Building evacuation in case of emergencies has long been recognized as a crucial issue, especially for the stair evacuation because evacuees may spend most of the evacuation time in stairs. To predict the evacuation time in stairs, simulations are commonly used, but known simulations ignore the stair structure and the fact that people may change their speeds during evacuation. As a result, how to introduce a reasonable mechanism on how evacuees change their speeds and improve the stair evacuation simulation ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Especially, because the space in a CA model is discrete and the same as that in a staircase, it is also used to simulate the pedestrian flow in stairs or escalators. [21,31,32] This improved CA model is based on the one considering evacuee's walk preferences of Ding et al [33,34] The cell size in the landing is 0.5 m×0.5 m and that in the steps is 0.5 m×0.28 m. From the experiment video data, it is found that there is one or two evacuees' lines in the step because the number of evacuees is not so large, which means that the extra 20-cm step width has no influence on the model. That is to say, the 1.2-m width step can be replaced with 2 cells.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, because the space in a CA model is discrete and the same as that in a staircase, it is also used to simulate the pedestrian flow in stairs or escalators. [21,31,32] This improved CA model is based on the one considering evacuee's walk preferences of Ding et al [33,34] The cell size in the landing is 0.5 m×0.5 m and that in the steps is 0.5 m×0.28 m. From the experiment video data, it is found that there is one or two evacuees' lines in the step because the number of evacuees is not so large, which means that the extra 20-cm step width has no influence on the model. That is to say, the 1.2-m width step can be replaced with 2 cells.…”
Section: Modelmentioning
confidence: 99%
“…In the Ding's model [34] evacuees' desiring to keep distance with others is introduced and the neighborhood around a pedestrian with two situations is defined. In this experiment, some new characteristics are found.…”
Section: Walk Preferencementioning
confidence: 99%
“…Chen et al ( 28 ) studied the route choice behavior of evacuees based on the preferential direction of pedestrians. In recent years, to quantify the effects of the evacuation environment, CA-based models were developed by taking social force into account ( 29 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The studies on pedestrian movements can be categorized as microscopic and macroscopic models [ 4 ]. Microscopic models include agent-based [ 8 ], cellular based [ 9 ], and lattice gas model based [ 10 ] simulation models. Queuing theory based models can be viewed as macroscopic models[ 11 ].…”
Section: Introductionmentioning
confidence: 99%